Recycling: A High‐Performance Recycling Solution for Polystyrene Achieved by the Synthesis of Renewable Poly(thioether) Networks Derived from d‐Limonene (Adv. Mater. 10/2014). (March 2014) - Hearon, Keith; Nash, Landon D.; Rodriguez, Jennifer N.; Lonnecker, Alexander T.; Raymond, Jeffery E.; Wilson, Thomas S.; Wooley, Karen L.; Maitland, Duncan J.
<x xml:space="preserve">Abstract</x> A materials engineering strategy that combines a breakthrough development in renewable polymer synthesis with an advancement in petroleum‐derived plastics recycling is reported by K. Hearon and co‐workers on page 1552: polymeric nanocomposites composed of a naturally derived rubber matrix phase and a recycled polystyrene precipitated phase are shown to exhibit mechanical behavior that greatly exceeds that of polystyrene and the naturally derived rubber alone. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>